Mass Transfer and Performance of Membrane-Less Micro Fuel Cell: A Review - M. N., Nasharudin; S. K., Kamarudin; U. A., Hasran; M. S., Masdar (Elsevier, 2014)
Membrane-less micro fuel cells (MMFCs) are high potential alternative power sources compared to conventional batteries. They use the advantage of laminar flow without the presence of a membrane to separate the anode and the cathode. This article is a wide-ranging review of recent studies on mass transfer, performance, modelling advances and future opportunity in MMFCs research. The discussion focuses on the critical factors that limit the performance of MMFCs. Because MMFCs are diffusion-limited, most of this review focuses on design considerations to enhance the power density output. Moreover, the current status of computational modelling for MMFC systems to upgrade the cell performance will be presented. The review also identifies the challenges and opportunities available for increasing cell performance and making the MMFC a practical application device in the future.